Frame importance valuation cognition based error control mechanism on cognitive networks - De-guang LE; Yong JIN; Dong-hui GUO; Jin-yi CHANG (Tongxin xuebao)
A cognitive error control mechanism for cognitive networks,called CEC was proposed.CEC was based on the cognition of importance of data frames’hops and types,which could select a best error control mechanism to improve the communication performance in cognitive networks.Besides,the energy efficiency model of cognitive networks was built.The mathematical analysis and simulation comparisons show that the proposed CEC mechanism achieves better performance in terms of communication reliability and energy efficiency in cognitive networks.